Relationship between Water Resource Utilization and Industrial Structure in Jiangxi Province - HU Jiuwei; CHENG Jingqing; LI Yanhong; XU Junkai; TAN Yi (Renmin Zhujiang)
With the introduction of the national rigid constraint system for water resources,industrial development is facing hard constraints from the red line of water resources.To improve the efficiency of water resource utilization and promote the coordinated development of water resources and industries,this paper uses the SBM model considering unexpected output super efficiency and the global ML index to measure the water resource utilization efficiency and its dynamic changes in Jiangxi Province from 2011 to 2020.The Thiel index and other indicators are adopted to analyze industrial structure and layout changes,and the grey correlation method is applied to evaluate the relationship of water consumption and water use efficiency with the development of three industries.Research has found that there is a strong correlation between water resource utilization and industrial structure,and there is a clear regional differentiation characteristic in the relationship between them.The overall correlation between water use efficiency and industrial structure in Jiangxi Province is slightly higher than that of water consumption.The primary industry has the highest correlation with water resource utilization,followed by the secondary and tertiary industries,and regional differences also exist in each city.The overall efficiency of water use continues to improve,and the industry is developing towards higher levels.However,there are problems such as regional imbalance and coordination.Finally,suggestions such as differentiated assessment are proposed.